Association of Dietary Branched-Chain Amino Acids With Obesity: The Filipino Women's Diet and Health Study (FiLWHEL). (7th June 2021) - Okekunle, Akinkunmi; Lee, Heejin; Provido, Sherlyn Mae; Chung, Grace; Hong, Sangmo; Yu, Sung Hoon; Lee, Chang Beom; Lee, Jung Eun
Abstract: Objectives: Migration plays a significant role in dietary choices and health of populations. Studies on dietary intakes of branched-chain amino acids (BCAA) and health status of migrant populations are scarce. This study examined the association between dietary BCAA intake and risk of obesity among migrant Filipino women in Korea. Methods: This study included 428 women (20–57years) enrolled in the FiLWHEL study. Demographic information and anthropometric measurements (weight and height) were obtained using a standard protocol. Dietary BCAA (isoleucine, leucine, and valine) intakes were derived from a one-day 24-hour dietary recall. Body mass index (BMI) was calculated from weight and height. Obesity was defined as BMI ≥ 25 kg/m 2 . Energy-adjusted BCAA intakes were categorized in quartile distribution with the lowest quartile as a reference and multivariable-adjusted odds ratio (OR) with 95% confidence interval (CI) of obesity risk were estimated using logistic regression at a statistical significance of P <  0.05 . Results: Mean age and BMI were 35.0 ± 8.1 years and 23.6 ± 3.9 kg/m 2  respectively. 30.8% had BMI ≥ 25 kg/m 2 . Also, median and interquartile range of BCAA intakes (mg/day) were isoleucine: 1920.9 (1231.9–2719.1), leucine: 3318.9 (2134.2–4774.1), valine: 2257.3 (1442.6–3283.1) and total BCAA: 7519.0 (4762.0–10, 726.9). Multivariable-adjusted OR and 95% CI for obesity risk given dietary BCAA intakes for each subsequent quartile compared to the bottom quartile were; isoleucine: 0.48 (0.27–0.89), 0.67 (0.37–1.02), and 0.49 (0.27–0.89) P for trend  = 0.09; leucine: 0.69 (0.37–1.28), 0.80 (0.44–1.46), and 0.62 (0.34–1.13) P for trend  = 0.23; valine: 0.51 (0.27–0.95), 0.77 (0.43–1.37), and 0.52 (0.28–0.95) P for trend  = 0.15 and total BCAA: 0.58 (0.31–1.09), 0.82 (0.45–1.48), and 0.56 (0.31–1.03) P for trend  = 0.23. Conclusions: Dietary BCAA intake appears inversely related to the odds of obesity in this sample of Filipino migrants in Korea. Cohort studies among migrant population might significantly benefit the validation of these observations. Funding Sources: This work was supported by the Hanmi Pharmaceutical Co., Ltd, (No. 201300000001270), Chong Kun Dang Pharm. Seoul, Korea (No. 201600000000225) and the Brain Pool Program through the National Research Foundation of Korea funded by the Ministry of Science and ICT (No. 2020H1D3A1A04081265).